2020
DOI: 10.1186/s40478-020-00954-1
|View full text |Cite
|
Sign up to set email alerts
|

The lipid phosphatase Synaptojanin 1 undergoes a significant alteration in expression and solubility and is associated with brain lesions in Alzheimer’s disease

Abstract: Synaptojanin 1 (SYNJ1) is a brain-enriched lipid phosphatase critically involved in autophagosomal/endosomal trafficking, synaptic vesicle recycling and metabolism of phosphoinositides. Previous studies suggest that SYNJ1 polymorphisms have significant impact on the age of onset of Alzheimer's disease (AD) and that SYNJ1 is involved in amyloid-induced toxicity. Yet SYNJ1 protein level and cellular localization in post-mortem human AD brain tissues have remained elusive. This study aimed to examine whether SYNJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 62 publications
(93 reference statements)
0
12
0
Order By: Relevance
“…The protein encoded by the SYNJ1 gene is a lipid phosphatase that is abundant in brain tissue and plays an important role in synaptic vesicle circulation and phosphatidylinositol metabolism (43). Previous studies have shown that SYNJ1 performs a critical regulatory role in the occurrence and development of various neurological diseases such as Alzheimer's disease and Parkinson's disease (44,45). Moreover, SYNJ1 also has an important regulatory effect on autophagy, and studies have shown that it is a regulatory factor with crucial involvement in the maturation of presynaptic terminal autophagosomes in Alzheimer's (46).…”
Section: Discussionmentioning
confidence: 99%
“…The protein encoded by the SYNJ1 gene is a lipid phosphatase that is abundant in brain tissue and plays an important role in synaptic vesicle circulation and phosphatidylinositol metabolism (43). Previous studies have shown that SYNJ1 performs a critical regulatory role in the occurrence and development of various neurological diseases such as Alzheimer's disease and Parkinson's disease (44,45). Moreover, SYNJ1 also has an important regulatory effect on autophagy, and studies have shown that it is a regulatory factor with crucial involvement in the maturation of presynaptic terminal autophagosomes in Alzheimer's (46).…”
Section: Discussionmentioning
confidence: 99%
“…SYNJ1 immunoreactivity is elevated in neurons and senile plaques in alzheimer disease patients with one or two apolipoprotein (APOE) ε4 alleles. 26 Phosphatidylinositol phosphatase synaptic binding protein 1 (SYNJ1), which regulates synaptic function, has been found to be negatively related to expression of synaptophysin, in postmortem brains of adult patients with Down syndrome (DS/alzheimer disease), by Miranda professor's. In mouse models studied by Professor Miranda, SYNJ1 overexpressing mice showed age-related cognitive decline to the level of human sporadic alzheimer disease, which is caused by hippocampal hyperexcitability and spatial reproducibility deficits in the position field.…”
Section: Discussionmentioning
confidence: 99%
“…SYNJ1 is expressed in neurons and is implicated in Aß toxicity (Berman et al, 2008 ), synaptic toxicity (McIntire et al, 2012 ) and Aß clearance (Zhu et al, 2013 ). The mRNA level of SYNJ1 is significantly upregulated in post-mortem AD brains in association with APOE genotype (Zhu et al, 2015 ; Ando et al, 2020 ). SYNJ1 protein undergoes a significant solubility change and is co-enriched with PHF-tau in the sarkosyl-insoluble fraction (Ando et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mRNA level of SYNJ1 is significantly upregulated in post-mortem AD brains in association with APOE genotype (Zhu et al, 2015 ; Ando et al, 2020 ). SYNJ1 protein undergoes a significant solubility change and is co-enriched with PHF-tau in the sarkosyl-insoluble fraction (Ando et al, 2020 ). SYNJ1 immunoreactivity is detected in actin-positive Hirano bodies, some NFTs and plaque-associated dystrophic neurites in post-mortem human AD brains (Ando et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation